The effect of commitment-making on weight loss and behaviour change in adults with obesity/overweight; a systematic review - Nia Coupe; Sarah Peters; Sarah Rhodes; Sarah Cotterill (BMC, 2019)
Abstract Background Adherence to weight loss interventions is crucial to successful outcomes, yet little is known about how best to improve it. This suggests a need for developing and improving adherence strategies, such as formal commitments. This review aims to identify the effect of including a commitment device alongside lifestyle interventions on weight loss, and identify the most appropriate delivery mechanisms and target behaviours. Methods We searched five databases and hand-searched reference lists for trials of behavioural interventions to achieve weight loss among adults with excess weight or obesity. Interventions incorporating commitment devices were included in a narrative review and meta-analysis where appropriate. Commitment devices with financial incentives were excluded. Results Of 2675 unique studies, ten met the inclusion criteria. Data from three randomised trials including 409 participants suggests that commitment interventions increases short-term weight loss by a mean of 1.5 kg (95% CI: 0.7, 2.4). Data from two randomised trials including 302 patients suggests that benefits were sustained at 12 months (mean difference 1.7 kg; 95% CI: 0.0, 3.4). Commitment devices appeared most successful when made publicly, and targeting diet rather than physical activity. Conclusions Using commitment devices, such as behavioural contracts, as part of a weight loss intervention may be useful in improving weight loss outcomes and dietary changes, at least in the short-term. However, evidence is limited and of variable quality so results must be interpreted with caution. Poor reporting of intervention details may have limited the number of identified studies. More rigorous methodology and longer term follow-ups are required to determine the effectiveness of behavioural contracts given their potential for use in public health interventions.